Postnatal Development of Pancreas in Non-Descript Pigs - Gross Anatomical Study - Shanthini S,; Rajathi S,; S, Muthukrishnan; Ninu A.R, (Indian Journal of Veterinary Anatomy, 2026)
The present research aimed to study the gross anatomy of pancreas in postnatal age groups ofnon–descript pigs. Pancreas in pig was located in the dorsal part of the abdominal cavity intimately related to theproximal part of the duodenum. Six pancreases were collected from each of three different age groups of pigsfrom the nearby slaughter houses. The pancreas of pigs appeared lobulated and triangular in shape. It was paleyellow, in neonatal group and yellowish cream colour, in young and adult ages. It was soft to touch duringpostnatal ages. The pancreas of pig was observed with three lobes namely splenic lobe, duodenal lobe, andconnecting lobe. Splenic lobe was the largest and formed not only one side of the triangle but also extended fromthe corresponding angle of the triangle. Duodenal lobe was associated with the duodenum. Connecting lobe wasthe smallest lobe. Two main ducts were observed; one as main pancreatic duct and the other as accessorypancreatic duct. The accessory pancreatic duct was found to be draining the pancreatic secretions of splenic lobeand the cranial part of duodenal lobe. It opened to the cranial part of duodenum and its opening was in the samelevel but opposite to the bile duct opening in all the postnatal ages studied. The main pancreatic duct was found tobe draining the pancreatic secretions from the caudal part of duodenal lobe, connecting lobe and bridge andopened at further caudal part of the duodenum.